Design study for hydraulic energy dissipator in streams using Autodesk CFD - Alejos López, Martín Sebastián; Trujillo Torres, Carlos Lenin; Carmona Arteaga, Abel (LACCEI, 2024)
The main objective of the research project is to analyze energy dissipation in streams to evaluate energy control, using the Autodesk CFD tool. The aim is to understand how energy dissipation can contribute to reducing the flow velocity of the water. Simulations will be conducted using Autodesk CFD, considering variables such as stream geometry, water flows, and the shape of the dissipators. The results of the simulations will allow for a better understanding of how the dissipators interact with the stream current. The theoretical framework will be based on academic sources that address key concepts of energy dissipation, flows, pressure, among others.